Cyclophosphamide for severe T-DXd-induced interstitial lung disease in low-HER2 breast cancer: a case report and mechanistic insights - Zhang, Weichun; Li, Xiaozhi; Zeng, De; Wang, Wende; Chen, Minna; Xue, Wenwu; Wen, Xiaofen; Lin, Danxia (Frontiers in Oncology, 2025)
BackgroundTrastuzumab deruxtecan (T-DXd) is an antibody-drug conjugate (ADC) that has shown significant efficacy in treating both HER2-positive and low-HER2 breast cancers. However, interstitial lung disease (ILD) remains a major adverse event associated with T-DXd treatment. Current management strategies for T-DXd-related ILD primarily rely on corticosteroids and immunoglobulins, with no established immunosuppressive regimen for steroid-refractory cases.Case descriptionA 49-year-old female with low-HER2 breast cancer developed Grade 4 ILD after receiving T-DXd treatment. She presented with severe respiratory symptoms, including chest tightness and hypoxia, and imaging revealed diffuse alveolar damage (DAD) pattern. Initial treatment with high-dose methylprednisolone and intravenous immunoglobulin showed limited improvement. Subsequently, low-dose cyclophosphamide (50 mg daily) was added, leading to rapid symptomatic and radiographic improvement. The patient’s condition stabilized, with significant reduction in lung inflammation, allowing for gradual tapering of corticosteroids and eventual discharge.ConclusionsThis is the first reported case of successful cyclophosphamide treatment for Grade 4 T-DXd-induced ILD in a low-HER2 breast cancer patient with severe liver metastases. It highlights the potential efficacy of cyclophosphamide in treating severe T-DXd-induced ILD, particularly in steroid-refractory cases. The mechanism may involve its ability to inhibit macrophage proliferation and promote anti-inflammatory effects. Further prospective studies are needed to validate the role of cyclophosphamide in managing T-DXd-related ILD and to explore risk stratification for optimal toxicity management.